Observed Changes in Extreme Temperature and Precipitation Indices on the Qinghai-Tibet Plateau, 1960–2016 - Gong, Xiangwen; Wang, Xuyang; Li, Yuqiang; Ma, Lei; Li, Manyi; Si, Hongtao (Frontiers in Environmental Science, 2022)
The Qinghai-Tibet Plateau, also known as the Earth’s “third pole”, is sensitive to climate change due to its extensive areas at high elevation, which are presently dominated by snow and ice. In this study, we investigated the spatial and temporal variation of 16 temperature and 11 precipitation extremal indices based on daily observations from 1960 to 2016 at 94 meteorological stations throughout the Qinghai-Tibet Plateau. The regionally averaged temperature index trends were consistent with global warming. The warmth indices, including the numbers of warm days, warm nights, summer days, and tropical nights showed significantly increasing trends. In contrast, the cold indices, including the numbers of cool days, cool nights, ice days, and frost days significantly decreased. The number of frost day and ice days showed the fastest decrease (3.9 and 2.7 days/decade, respectively), whereas the growing season length showed the fastest growth trend (2.8 days/decade). The warming trend strengthened with increasing latitude, and the occurrences of daytime extreme temperature events increased with increasing longitude. In addition, the frequency and intensity of cold temperature events increased at high elevations, whereas warm temperature events showed the opposite trend. The regionally averaged monthly maximum 1-day precipitation and maximum consecutive 5-day precipitation increased by 0.17 and 0.70 mm per decade, respectively. In contrast, the number of consecutive dry days (CDD) and consecutive wet days (CWD) decreased at rates of 1.11 and 0.03 days per decade, respectively. The extreme precipitation events were more frequent in low-latitude and high-longitude regions.